2022
DOI: 10.3390/metabo12030196
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Protein Biomarkers of β-Cell Function in Type 2 Diabetes and Their Modulation with Glucose Normalization

Abstract: Development of type-2 diabetes(T2D) is preceded by β-cell dysfunction and loss. However, accurate measurement of β-cell function remains elusive. Biomarkers have been reported to predict β-cell functional decline but require validation. Therefore, we determined whether reported protein biomarkers could distinguish patients with T2D (onset < 10-years) from controls. A prospective, parallel study in T2D (n = 23) and controls (n = 23) was undertaken. In T2D subjects, insulin-induced blood glucose normalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Interestingly, elevated E-cadherin levels have been proposed as a prognostic protein for type 2 diabetic patients [31]. It is known that the principal type of cadherin present in pancreatic islet is E-cadherin and it has an important role in islet formation [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, elevated E-cadherin levels have been proposed as a prognostic protein for type 2 diabetic patients [31]. It is known that the principal type of cadherin present in pancreatic islet is E-cadherin and it has an important role in islet formation [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…43 Insulin-like growth factor binding protein 1, as well as IGFBP-2 through 5, may have IGF-independent associations with glucose uptake and insulin sensitivity and have been associated with the pathogenesis of metabolic syndrome, diabetes, and diabetes complications. 11,12,[44][45][46][47][48][49] JAMA Network Open | Diabetes and Endocrinology…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-like growth factor binding protein 1 modulates IGF-1 bioavailability and has been shown to inhibit IGF-1 effects, which may explain the inverse association between the 2 hormones in our analysis . Insulin-like growth factor binding protein 1, as well as IGFBP-2 through 5, may have IGF-independent associations with glucose uptake and insulin sensitivity and have been associated with the pathogenesis of metabolic syndrome, diabetes, and diabetes complications …”
Section: Discussionmentioning
confidence: 99%
“…Notably, multivariate logistic ordinal regression analysis revealed that an increase in serum endocan levels by one unit resulted in a two-fold increase in the odds of higher HbA1c levels [ 7 ], suggesting an interconnection between this novel biomarker of endothelial dysfunction with poor glycemic control in T2DM. Of note, in a more recently published case-control study recruiting 23 patients with T2DM and 23 healthy controls, it was shown that plasma endocan levels were significantly lower in T2DM patients compared to controls, while they remained unchanged after hyper-insulinemic euglycemic clamp, a finding suggestive of an absence of a relationship between circulating endocan levels and glycemic variability [ 43 ]. However, according to previous data retrieved from a proteomics and miRNA profiling analysis in a total of 1157 subjects without baseline T2DM from the Relationship between Insulin Sensitivity and Cardiovascular disease (RISC) cohort, it has been documented that endocan might even be a prognostic marker of the decline in β-cell function and the development of impaired glucose tolerance and T2DM [ 44 ].…”
Section: Endocan and Type 2 Diabetes Mellitusmentioning
confidence: 99%